Auricular Reconstruction and Postoperative Wound Care in Necrotizing Fasciitis Secondary to Malignant Otitis Externa in a Diabetic Patient with Scabies - Amira Azra Arisa Putri; Mufida Muzakkie; Ratna Maila Dewi Anggraini; Fadel Fikri Suharto (The Lingkar Studi Bedah Plastik Foundation and is affiliated with the Department of Plastic Surgery, Faculty of Medicine, Universitas Indonesia., 2026)
Introduction: Necrotizing fasciitis of the auricle and periauricular region is extremely rare but life-threatening, typically affecting immunocompromised patients and occasionally complicating malignant otitis externa. Its aggressive progression and the auricle's complex anatomy demand early diagnosis and prompt multidisciplinary management to prevent extensive tissue loss.Case presentation: We report auricular necrotizing fasciitis secondary to malignant otitis externa in a 55-year-old patient with poorly controlled diabetes mellitus and concomitant scabies infestation. The infection progressed rapidly, causing necrosis of the auricle and surrounding soft tissues. Culture identified Pseudomonas aeruginosa as the causative pathogen. Management included targeted systemic antibiotics, strict glycemic control, and early staged surgical debridement. The plastic surgery team performed selective staged debridement, removing non-viable tissue while maximally preserving viable auricular cartilage. Postoperative care employed honey-based dressings to control infection and promote granulation.Conclusion: This case demonstrates the synergistic effects of diabetes mellitus and scabies in predisposing patients to severe infections and impairing wound healing. An early plastic surgery consultation facilitated anatomically precise debridement, preservation of the auricular contour, and avoidance of radical excision. Auricular necrotising fasciitis remains a surgical emergency requiring timely multidisciplinary intervention and tailored wound management to optimise functional and aesthetic outcomes in high-risk patients.